Improving assessment of postoperative pain in surgical wards by education and training. Issue 5 (29th September 2005) - Karlsten, R; Ström, K; Gunningberg, L
Abstract : Problem: There is a need to improve postoperative pain organisation and management in hospitals. One of the most important factors in achieving this is to improve active assessment of pain in the postoperative phase. Design: Repeated audits on an annual basis over a 3 year period. Ward nurses, appointed as "pain control representatives", performed the data collection. Setting: Departments of general surgery and orthopaedics in a university hospital with 1200 beds. Key measure for improvement: Assessment of postoperative pain intensity using a numerical rating scale. Strategies for change: On the basis of the first audit in 1999 the team decided to introduce a mandatory training programme in postoperative pain management for all involved staff, including surgeons and ward nurses. Guidelines for postoperative care were upgraded and made accessible through the intranet. Regular staff meetings in the surgical wards with representatives from the acute pain service team were introduced. Effects of change: The assessment of pain according to protocols increased from 71% to 91% in the surgical wards and from 60% to 88% in the orthopaedic wards between 1999 and 2001/2. Lessons learnt: To increase the awareness of pain and improve pain assessment, the importance of mandatory training, regular staff meetings and regular audits must be emphasised. It is also imperative to give feedback on the regular audits to the ward and staff members involved.